EFFECT OF PSYCHROTROPHIC BACTERIAL CONTAMINATION OF RAW MILK ON ORGANIC ACID CONTENT ‎AND FLAVOROF AGED CHEDDAR CHEESE - H. Najim, Najim; H. White, Charles (The Iraqi Journal of Veterinary Medicine, 1987)
Cheddar cheese was made from milk which had been inoculated with psychrotrophs 48hr.. prior to pasteurization. This was compared to ‘control cheese. The cheese was stored at 7 °C and evaluated at 0, 5, 30, 60 and 180 days. ‘All cheese made with psychrotroph-treated milk had significant lower flavor score than control cheese. The predominant flavors of the 180 day-treated cheese were bitter and unclean. High performance. liquid chromatography (HPLC) analysis indicated significant increases of citric, pyruvic, lactic, formic, acetic and propionic acids with ‘aging of Cheddar cheese. Only orotic acid decreased with aging. The control cheese had lower values than the treated cheese for pyruvic, lactic and formic acids. The control cheese had higher propionic acid value than did the treated cheese.The aroma and flavor quality of Cheddar cheese was attributed to a delicate balance of organic acids produced as metabolites by culture bacteria during fermentation.